2016
DOI: 10.3892/ol.2016.4851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined sunitinib and extracranial stereotactic radiotherapy on bone marrow hematopoiesis

Abstract: Abstract. There is considerable interest in deploying stereotactic body radiotherapy in combination with immune therapy for patients with extracranial oligometastases. In addition to angiogenesis inhibition, sunitinib appears to mediate antitumor immunity through effects on circulating monocytic cells. The current study investigated the effects of combined sunitinib and stereotactic radiotherapy on hematopoiesis. As part of a phase I/II clinical trial utilizing concurrent sunitinib (25-50 mg on days 1-28) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Although neutrophils and lymphocytes are non-specific parameters that are affected by concurrent infection, inflammation, corticosteroids, chemotherapy and radiation therapy, baseline NLR is a promising, readily available and cost-effective biomarker that adds prognostic value to known clinical and laboratory prognostic factors (3,8,18). In the present study, patients with an NLR >4 with metastatic disease that were referred to radiation oncology had a median survival of 4.1 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although neutrophils and lymphocytes are non-specific parameters that are affected by concurrent infection, inflammation, corticosteroids, chemotherapy and radiation therapy, baseline NLR is a promising, readily available and cost-effective biomarker that adds prognostic value to known clinical and laboratory prognostic factors (3,8,18). In the present study, patients with an NLR >4 with metastatic disease that were referred to radiation oncology had a median survival of 4.1 months.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of baseline NLR has been demonstrated in 100 studies for several types of solid tumors (3). To date, limited data has been provided for NLR in patients treated with radiation, particularly in those with metastatic solid tumors (8,9). Previous studies have demonstrated that patients with metastatic disease treated with radiation tend to have a baseline NLR of 4-5 (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three percent of patients experienced toxicity of grade 3 or higher, and 2 fatal hemorrhages were recorded. Surprisingly, compared to sunitinib alone, the sunitinib-RT combination resulted in further reduction in hemo poiesis [19]. …”
Section: Resultsmentioning
confidence: 99%
“…Regorafenib hematological toxicity has been explained by the TK inhibition of FMS like tyrosine kinase 3 (FLT-3) and stem cell factor (c-KIT ligand), which represent hematopoietic growth receptors (15, 16). Reduction in the circulating monocyte count after sunitinib has been shown (17). Monocytes are also highly sensitive to the methylating agent temozolomide (TMZ) (18, 19).…”
Section: Introductionmentioning
confidence: 99%